Experimental and Theoretical Testing Results of Reinforced Concrete Columns under Biaxial Bending - Pavlikov, Andriy; Harkava, Olha; Prykhodko, Yulia; Baryliak, Bohdan (International Journal of Engineering and Technology, 2018)
The experimental tests data of reinforced concrete columns of a rectangular profile made of heavy concrete on biaxial bending with axial force are presented. The inclination angle of the external load plane to the vertical axis of inertia of the section varied in the range from 14Âº to 66Âº. The tests were conducted to study the work of the biaxial bended elements under load and to verify the developed method for strength analysis of such elements. It has been confirmed that the ultimate compressed fibrous strains of concrete depend not on the shape of the section, but on the shape of the concrete compressed area. The general method of strength analysis of biaxial bended reinforced concrete columns is developed. The problem of difficulty applying nonlinear deformation model in the study of biaxial deformed elements is successfully solved by the introduction of the stress-strain relations for concrete and reinforcement and extremal strength criterion. The results of the tests have good correspondence with theoretical calculations, which proves the expediency of using the developed method for the strength analysis.Â Â Â